Selection of the biological activity of DNJ neoglycoconjugates through click length variation of the side chain. - Ardes-Guisot, N; Alonzi, D; Reinkensmeier, G; Butters, T; Norez, C; Becq, F; Shimada, Y; Nakagawa, S; Kato, A; Blériot, Y; Sollogoub, M; Vauzeilles, B (2011)
A series of neoglycoconjugates derived from deoxynojirimycin has been prepared by click connection with functionalised adamantanes. They have been assayed as glycosidase inhibitors, as inhibitors of the glycoenzymes relevant to the treatment of Gaucher disease, as well as correctors of the defective ion-transport protein involved in cystic fibrosis. We have demonstrated that it is possible to selectively either strongly inhibit ER-α-glucosidases and ceramide glucosyltransferase or restore the activity of CFTR in CF-KM4 cells by varying the length of the alkyl chain linking DNJ and adamantane.